Public Transport or a Landmine: Insecurities, Harassment and its Effect on Mental Health in Women Using Public Transport System in Chennai District, Tamil Nadu - Sushmitha Govindaraj; Anantha Eashwar VM; Sujitha P; Umadevi R; Monica Albert Sekhar; Shirley Esther Priscilla; Swathika Devi R (Masters Program in Public Health, 2024)
Background: Crimes against women committed while traveling in public transportation is seldom understood, analyzed, and reported. The World Health Organization has stated that any form of violence against women must be considered a public health emergency. As a result of abuse, their overall health is impacted. This study was conducted to find the prevalence of insecurity and characterization of harassment among female passengers while traveling on public transport.Subjects and Method: The cross-sectional study was conducted in the Chennai district, Tamilnadu between November 2023 to March 2024. A total of 270 women above 18 years of age and using public transport for a minimum period of 6 months for daily commuting were included as study participants selected using a simple random sampling method. Data related to Subjective fear of traveling alone in public transport was used as a dependent variable which was collected using a pre-tested semi-structured questionnaire comprised of questions related to sociodemographic characteristics, having faced verbal/physical harassment, and having experienced stalking while traveling in public transport, which were used as independent variables. Subjective response to harassment was assessed using the Impact of Event Scale-Revised (IES-R). Data was analyzed using SPPS version 26. Chi-square and logistic regression analysis were used to find the predictors that lead to the fear of traveling alone.Results: A total of 270 participants were included in the study. The predictors for developing fear of travelling alone in public transport system were, belonging to a nuclear family (aOR= 2.12; 95% CI= 1.23 to 3.32), women who faced any kind of harassment (aOR= 2.56; 95% CI= 1.76 to 3.84), faced physical harassment (aOR= 3.92; 95% CI= 2.45 to 5.67) and faced verbal harassment (aOR= 4.11; 95% CI= 1.87 to 6.34).Conclusion: It’s not only enough to bring about policies, but the common public must be educated about harassments that happen on public transport. A special task force must be formed to apprehend the assailants.